Thymus of Buffalo: Ultra Structural Perspective - Parkash, Tej; Poonia, Amit; Gahlot, Parveen Kumar (Indian Journal of Veterinary Anatomy, 2026)
Ultrastructural features of the thymus were studied in five young buffalo with age ranges from 1 to 1.5 years old. In the cortex, densely packed thymocytes (lymphocytes) in various stages of differentiation were observed. The shapes of thymocytes were round to elliptic in outline. The cytoplasm was poor in terms of organelles. Thymic epithelial cells (TEC) were also observed throughout the cortex. They were characterised by pale, electron-lucent cytoplasm, irregular shape with long cytoplasmic processes connected to each other by desmosomes to form a reticular network. In medulla, a loose arrangement of mature thymocytes, and medullary thymic epithelial cells (TECs) were observed. There was degenerative nuclear and cytoplasmic structure in the central part of Hassall’s corpuscles. Additionally, other cell types within the thymus, including macrophages and mast cells, which contribute to the phagocytic clearance of apoptotic thymocytes and antigen presentation were also observed.